Bioengineered Indoor Farming Approaches: LED Light Spectra and Biostimulants for Enhancing Vindoline and Catharanthine Production in Catharanthus roseus - Alessandro Quadri; Bianca Sambuco; Mattia Trenta; Patrizia Tassinari; Daniele Torreggiani; Laura Mercolini; Michele Protti; Alessandra Zambonelli; Federico Puliga; Alberto Barbaresi (Horticulturae)
Light quality and biostimulants regulate alkaloid biosynthesis and promote plant growth, but their combined effects on vindoline (VDL) and catharanthine (CAT) production in Catharanthus roseus remain underexplored. This study investigated the impact of different LED spectra and an arbuscular mycorrhizal fungi-based biostimulant (BS) on VDL and CAT production in indoor-grown C. roseus. After a 60-day pretreatment under white LEDs, plants were exposed to eight treatments: white (W, control), red (R), blue (B), and red-blue (RB) light, and their combinations with BS. Samples were collected before treatments (T0) and 92 days after pretreatment (T1). No mycorrhizal development was observed. VDL was detected in both roots and leaves, with higher levels in roots. R produced significantly higher mean concentrations of both VDL and CAT than W. BS significantly increased mean concentrations and total yields of both alkaloids than the untreated condition. The combination of R and BS produced the highest mean concentrations and total yields of VDL and CAT. In particular, it resulted in a significantly higher mean concentration and total yield of VDL compared to sole W. Total yields increased from T0 to T1, primarily due to a substantial rise in root yield. In conclusion, combining R and BS proved to be the most effective strategy to enhance VDL and CAT production by maximizing their total yields, which also increased over time due to greater root contribution. This underscores the importance of combining targeted treatments with harvesting at specific stages to optimize alkaloid production under controlled conditions.